EHealth interventions to facilitate work participation: a scoping review protocol. (June 2019) - Øyeflaten, Irene; Johansen, Thomas; Nielsen, Claus Vinther; Johnsen, Tone Langjordet; Tveito, Torill Helene; Momsen, Anne-Mette Hedeager
Abstract : Review question: The objective of this scoping review is to identify and synthesize existing literature on the different types of eHealth interventions used in workplaces and healthcare settings to facilitate work participation. The following questions will be examined: For which user groups, in which settings and by which stakeholders are eHealth interventions provided? Are eHealth interventions that are aimed at work participation theory-driven or based on empirical evidence?